2020
DOI: 10.1111/iwj.13494
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy for patients with mediastinitis: A meta‐analysis

Abstract: To evaluate clinical effects between conditional treatment and negative pressure wound therapy for mediastinal infection. Multiple databases were searched to identify relevant studies, and the articles that eventually satisfied the criteria were included. All the meta‐analyses were conducted with the Review Manager 5.2. To estimate the quality of each article, risk of bias table was performed. Finally, nine studies including 648 patients met the eligibility criteria. The negative pressure wound therapy (NPWT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…[20][21][22] A study indicated that VSD can shorten the time of the first skin graft. 23 Similarly, the results of this study showed that VSD can accelerate the growth of wound granulation tissue and reduce the time of the first skin graft. Continuous closure of VSD can draw out interstitial fluid from the wound, thereby reducing the pressure in blood vessels and improving blood circulation.…”
Section: Discussionsupporting
confidence: 61%
“…[20][21][22] A study indicated that VSD can shorten the time of the first skin graft. 23 Similarly, the results of this study showed that VSD can accelerate the growth of wound granulation tissue and reduce the time of the first skin graft. Continuous closure of VSD can draw out interstitial fluid from the wound, thereby reducing the pressure in blood vessels and improving blood circulation.…”
Section: Discussionsupporting
confidence: 61%
“…When the tissue is damaged or infected by toxins or bacteria, damaged by heat or other causes, it will enter the normal state of self-protection and damage repair. Therefore, IR is also a defensive response of human body to stimuli [ 23 , 24 ]. It was found that IR score in the Exp group was much lower than that in the Ctrl group at week 1 and 2 after treatment, and the difference was statistically significant ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The distinctiveness and clinical relevance of our research lie in its detailed investigation and analysis of factors contributing to PWIs in lung cancer surgery. By employing both univariate and multivariate analyses, our study offers a comprehensive view of the complex interplay between various clinical and patient‐specific factors 21,22 …”
Section: Discussionmentioning
confidence: 99%